Aluminum granuloma in a child secondary to DTaP‐IPV vaccination: A case report. Issue 1 (28th November 2018) - Haag, Carter K.; Dacey, Elizabeth; Hamilton, Nick; White, Kevin P.
Abstract: Reports detailing the acute formation of aluminum granulomas, which can cause persistent, intensely pruritic nodules secondary to the administration of aluminum‐containing vaccines, are infrequently described in medical literature. To our knowledge, this is the first report describing the development of an aluminum granuloma causing a persistent, pruritic nodule at the injection site following the administration of the DTaP‐IPV vaccine. We present the case of a 6‐year‐old girl who developed a severely pruritic subcutaneous nodule on her anterior right thigh at the injection site three weeks after the administration of the aluminum‐containing DTaP‐IPV (Kinrix) vaccine. The nodule was eventually excised 14 months after its initial appearance, after which her symptoms resolved. Histologic inspection demonstrated a dense, deep dermal and subcutaneous nodular mixed infiltrate of lymphocytes, histiocytes, and eosinophils, with germinal center formation. The bluish, amphophilic granular cytoplasm found in most of the histiocytes is a characteristic feature of "aluminum granulomas." This adverse reaction should be considered in any patient presenting with similar findings in the weeks following a DTaP‐IPV vaccination or other aluminum‐containing vaccines. Furthermore, the self‐limiting tendency of these nodules should not preclude affected patients from any future vaccinations, though vaccines without aluminum should be preferentially selected when possible.